Comparison of different methods for identification of meat species in meat products - Yusuf Özşensoy; Seyda Şahin (Eurasian Journal of Veterinary Sciences)
Aim: Objective of this study were identification of animal species in meat products marketed in Sivas province using different methods and comparison of these methods. Materials and Methods: Sucuk, salami, sausage, meatball and braised meat samples were collected for the investigation from marketed in Sivas province with random samples methods in 2014. The identification of meat species in meat products was investigated using Agar Gel Immunodiffusion (AGID), and Enzyme-Linked Immunosorbent Assay (ELISA) and Polymerase Chain Reaction (PCR) methods. Results: All of AGID, ELISA and PCR methods detected positivity for cattle meat in same samples. Three samples (two salami and one sucuk) were detected negative for cattle meat with ELISA. According to the PCR results, total of 11 different samples together these three samples were detected as small ruminants (sheep/goat) residues. And there samples were detected as poultry (chicken) residues. None of the samples were detected as positive for pig, horse and carnivore (cat) meats by all three methods. Conclusions: Besides three methods used being compatible with each other, the PCR method was found more sensitive. The absence of residues of unwanted species in meat products which are commonly consumed in Sivas province, it is important for public health; also sensitivity of companies to provide reliable products and it may be related with intensity of inspections and applying of Meat and Meat Products Notification since March 1, 2013.